Teachers Strategy, Challenges on Pupils Numeracy Disciplines at the Intermediate Level - Sabuclalao, Jimboy L.; Lantaka, Ivy A. (International Journal of Research in Interdisciplinary Studies, 2025)
Numeracy is a critical foundation for academic success and everyday life, yet many students continue to face difficulties in mastering essential mathematical skills, particularly those affected by poverty. Addressing this concern, the present study, titled *“Teachers' Strategies and Challenges on Pupils' Numeracy Disciplines at the Intermediate Level,”* aimed to determine the specific numeracy challenges faced by Grade 6 learners at Labuan Central School, Zamboanga City, for the school year 2024–2025. The research focused on assessing the extent of teachers' teaching strategies in terms of instructional methods, assessment and feedback, and learners’ outcomes, as well as examining the correlation between these strategies and students' mathematics proficiency. The study was limited to Grade 6 learners and did not extend to other grade levels or schools. A descriptive-correlational research design was employed, involving 96 learners selected through purposive sampling based on Gay’s (1997) recommendation. Data were collected using a researcher-adapted questionnaire, administered after obtaining the necessary approvals from education authorities. The findings revealed that although teachers applied diverse instructional approaches and provided assessments, learners continued to face challenges such as difficulty in understanding word problems, managing math-related anxiety, and keeping up with lesson pacing. A significant positive relationship was found between teachers' strategies and students' math proficiency. Based on these findings, the study recommends strengthening guided practice, improving feedback mechanisms, building learner confidence, adopting differentiated instruction, enhancing resources, providing continuous teacher development, and fostering a supportive learning environment to advance numeracy skills, especially for learners affected by poverty.